REPRESENTASI IDENTITAS LOKAL DAN PERLAWANAN BUDAYA DALAM PATUNG MACAN KURUNG JEPARA - Wisnu Adisukma (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Macan Kurung statue is a distinctive cultural artifact from Jepara, which is now becoming increasingly rare. This study aims to reveal a discourse of self-representation and counter-culture, constructed by the socio-cultural conditions of Javanese society during the colonial period. The research employs a qualitative method with an ethnographic approach and cultural semiotic analysis. Data were collected through observation, document studies, and in-depth interviews with heirs and artisans. The results indicate that the Macan Kurung Statue is not merely an aesthetic product but a visual narrative containing an anti-colonial message. Moreover, after R.A. Kartini took a role in making the Tiger Statue which was guided directly by Singowiryo. Through the symbols of a caged and chained tiger, a mighty Garuda bird, and a dragon. It’s founders, Asmo Sawiran and Singowiryo, conveyed criticism ofvcolonialism and an effort to reaffirm the legitimacy of Javanese culture as an adiluhung (sublime and majestic) and dynamic entity amidst the penetration of foreign cultures. These findings contribute significantly to the understanding of the role of folk art as a medium for political expression and a guardian of cultural identity.